The Mikulicz Cell in Rhinoscleroma: Light, Fluorescent and Electron Microscopic Studies - Hoffmann, Ernesto O. (1973)
The stages in the development of the Mikulicz cell in human rhinoscleroma were studied in biopsy specimens obtained from 10 patients using light, immunofluorescent and electron microscopy. The Mikulicz cell was identified morphologically as a macrophage, not a plasma cell. Acutely inflamed areas of rhinoscleroma presented abundant bacteria with a slime layer. The microorganism was infrequent and the mucopolysaccharide was scanty in rhinoscleromal tissue, where plasma cells predominated, and in cicatricial fibrous tissue. In the granulomatous stage of rhinoscleroma, the mucopolysaccharide was found within the Mikulicz cells. The vacuoles observed in the Mikulicz cells were considered to be phagosomes containing, principally, bacterial mucopolysaccharide and few bacteria and, to a lesser extent, swollen mitochondria. It was concluded that the slime layer of Klebsiella rhinoscleromatis plays an important role in the pathogenesis of the disease. It is postulated that this material is a nondigestible mucopolysaccharide that resides in the phagosomes of macrophages, increases the osmotic pressure and forms multiple hydropic vacuoles that rupture not only the phagosomes but also the cells, resulting in the liberation of the mucopolysaccharide. This would initiate a cycle that would prolong the disease in the absence of the bacteria.